2016
DOI: 10.1039/c6fo00239k
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the release of dipeptidyl peptidase IV (DPP-IV) inhibitory peptides in an enzymatic hydrolyzate of α-lactalbumin

Abstract: Bovine α-lactalbumin (α-La) contains numerous dipeptidyl peptidase IV (DPP-IV) inhibitory peptides sequences within its primary structure. In silico analysis indicated that the targeted hydrolysis of α-La with elastase should release DPP-IV inhibitory peptide sequences. An α-La isolate was hydrolysed with elastase under different conditions using an experimental design approach incorporating 3 factors (temperature, pH and enzyme to substrate ratio (E:S) ratio) at 2 levels. The hydrolyzate generated at pH 8.5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
(75 reference statements)
2
23
0
Order By: Relevance
“…In the present study, bovine α-lactalbumin hydrolysates were obtained by alcalase, and the DPP-IV inhibitory activity was determined. Our results showed that 4 h hydrolysates possessed the strongest DPP-IV inhibitory activity with inhibition rate of 82.30 ± 1.39% at a concentration of 1.0 mg/mL (Figure 1), which was higher than that of bovine α-lactalbumin hydrolysate generated by elastase (with DPP-IV inhibition rate of 75.8 ± 3.7% at a concentration of 3.1 mg/mL) [24].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In the present study, bovine α-lactalbumin hydrolysates were obtained by alcalase, and the DPP-IV inhibitory activity was determined. Our results showed that 4 h hydrolysates possessed the strongest DPP-IV inhibitory activity with inhibition rate of 82.30 ± 1.39% at a concentration of 1.0 mg/mL (Figure 1), which was higher than that of bovine α-lactalbumin hydrolysate generated by elastase (with DPP-IV inhibition rate of 75.8 ± 3.7% at a concentration of 3.1 mg/mL) [24].…”
Section: Discussionmentioning
confidence: 70%
“…Among the two identified peptides shown in Table 1 , peptide ILDKVGINY has been demonstrated with DPP-IV inhibitory activity previously (IC 50 values = 263 μM) [ 22 ]. As for peptide ELKDLKGY, although it has not been mentioned in the literature previously, it contains the same amino acid sequences with several reported DPP-IV inhibitory peptides, such as RELKDLKGY, RELKDLKGYG, RELKDLKGYGG, RELKDLKGYGGVS, RELKDLKGY, KDL, KGY, and GY [ 22 , 24 ]. Various studies showed that the peptides displaying potent DPP-IV inhibitory activity generally have a length of 2 to 7 amino acids [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches are based on peptide cutters used in in silico digestion of selected food proteins to predict the release of target peptides (known DPP‐IV inhibitory peptides or peptides possessing features of DPP‐IV inhibitory peptides). Information generated by peptide cutters has been described during the hydrolysis of bovine α‐lactalbumin (α‐La) with porcine pancreatic elastase (Nongonierma, Le Maux, Hamayon, & FitzGerald, ). However, it was found that only 60% of the peptides predicted to be released in silico were actually identified by liquid chromatography tandem mass spectrometry (LC‐MS/MS) in the bovine α‐La hydrolysate.…”
Section: Targeted Generation Of Dpp‐iv Inhibitory Peptides During Hydmentioning
confidence: 99%
“…In Gottingen minipigs, bovine α-lactalbumin reduced serum haptoglobin and C-reactive protein level, resulting in the amelioration of Western diet-induced glucose intolerance [ 23 ]. Furthermore, peptides derived from bovine α-lactalbumin inhibited dipeptidyl peptidase 4 (DPP-4) activity, suppressed angiotensin converting enzyme (ACE) activity, scavenged 2,2′-azinobis [3-ethylbenzothiazoline-6-sulfonate] (ABTS + ) radical and stimulated glucagon-like peptide-2 secretion [ 24 , 25 , 26 , 27 , 28 ]. However, there are few studies about the efficacy and underlying mechanisms of bovine α-lactalbumin hydrolysates against insulin resistance.…”
Section: Introductionmentioning
confidence: 99%